Pelatihan Pijat Bayi Sehat pada Kader Kesehatan di Loli Kecamatan Banawa Kabupaten donggala : Healthy Baby Massage Training for Health Cadres in Loli, Banawa District, Donggala Regency - Taqwin Taqwin; Linda Linda; Lili Suryani; Ita Sulistiani (Poltekita: Jurnal Pengabdian Masyarakat, 2022)
One touch stimulation that has a positive impact on babies is massage. Infant massage training can increase the knowledge and skills of cadres. The health cadres at Loli have never received training in healthy baby massage. The purpose of community service is to increase the knowledge and skills of health cadres through healthy baby massage training in Loli, Banawa District, Donggala Regency. The service method is a healthy baby massage training which will be held on June 22, 2022. The target of the training is health cadres, totaling 20 participants. The result of the training is an increase in the knowledge and skills of the participants. Before the training 2 participants had good grades and 18 participants had less. After the training, the score was good 12 participants and less than 8 participants. Healthy baby massage training improves the knowledge and skills of health cadres in Loli, Donggala Regency. It is recommended that health cadres continue to practice healthy baby massage through the modules provided and the health center through village midwives supervise the implementation of healthy baby massage. ABSTRAK Salah satu stimulasi sentuh yang memberikan dampak positif bagi bayi adalah pijat. Pelatihan pijat bayi dapat meningkatan pengetahuan dan keterampilan kader. Kader kesehatan di Loli belum pernah mendapatkan pelatihan pijat bayi sehat. Tujuan pengabdian masyarakat adalah meningkatnya pengetahuan dan keterampilan kader kesehatan melalui pelatihan pijat bayi sehat di Loli Kecamatan Banawa Kabupaten Donggala. Metode pengabdian adalah pelatihan pijat bayi sehat yang dilaksanakan pada 22 Juni 2022. Sasaran pelatihan adalah kader kesehatan yang berjumlah 20 peserta. Hasil pelatihan adalah meningkatnya pengetahuan dan keterampilan peserta. Sebelum pelatihan 2 peserta memiliki nilai baik dan 18 peserta kurang. Setelah pelatihan, nilai baik 12 peserta dan kurang 8 peserta. Pelatihan pijat bayi sehat meningkatkan pengetahuan dan keterampilan kader kesehatan di Loli Kabupaten Donggala. Disarankan agar kader kesehatan terus berlatih pijat bayi sehat melalui modul yang diberikan dan pihak puskesmas melalui bidan desa melakukan pengawasan pelaksanaan pijat bayi sehat.